High‐Voltage Li‐Ion Full‐Cells with Ultralong Term Cycle Life at Elevated Temperature. Issue 33 (7th October 2018) - Qiao, Yu; He, Yibo; Jiang, Kezhu; Liu, Yang; Li, Xiang; Jia, Min; Guo, Shaohua; Zhou, Haoshen
Abstract: In order to meet the ever‐growing demand for energy and power densities in rechargeable lithium‐ion batteries for electric vehicles, intensive research efforts are focusing on increasing output voltage and maintaining high capacity. However, the trade‐off for higher voltage is sacrificing the service life of the batteries, since the detrimentally oxidative degradation on the high‐potential cathode side would inevitably poison the whole cell. Thus, optimizing strategies for full‐cells must take into account, cathode/anode‐electrolyte compatibilities, electrochemical reversibility, and even thermal stability for practical applications, which spurs a hierarchical design for full‐cell architecture. Benefitting from its superior oxidative stability, ionic liquid (Li/Pyr13 TFSI) is employed as catholyte, and equimolar LiTFSI/G3 complex is used as anolyte due to its high graphite‐intercalation‐chemistry reversibility. Segregated by a metal–organic‐framework‐based separator, advantages and drawbacks of each electrolyte systems can be synergistically tuned within their isolated environments. Encouragingly, assembled by this hybrid‐electrolytes strategy, a LiNi0.5 Mn1.5 O4 (5 V‐class)/graphite Li‐ion full‐cell holds an ultrahigh capacity retention rate of 83.8% over 1000 cycles at harsh elevated temperature. Abstract : A hybrid electrolytes design is introduced into a high‐voltage Li‐ion full‐cell system. The oxidative stability of ionic liquid (catholyte) supports the 5 V‐class LiNi0.5 Mn1.5 O4 cathode working at elevated temperature, while good Li‐graphite‐intercalation‐chemistry reversibility of super‐concentrated ether electrolyte (anolyte) is beneficial to the graphite anode. By the employment of metal–organic‐framework‐based separators, each electrolyte can be well separated from corresponding electrodes.